2013
DOI: 10.3390/molecules18043779
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase Enzymes Inhibitors from the Leaves of Rauvolfia Reflexa and Their Molecular Docking Study

Abstract: Plants of the Apocynaceae family have been traditionally used in the treatment of age-related brain disorders. Rauvolfia reflexa, a member of the family, has been used as an antidote for poisons and to treat malaria. The dichloromethane, ethanol and methanol extracts from the leaves of Rauvolfia reflexa showed potential acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory activities, with IC50 values in the 8.49 to 52.23 g/mL range. Further cholinesterase inhibitory-guided isolation of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Acorenone B showed an inhibitory activity against AChE and BChE with IC 50 concentrations of 40.8 and 10.9 μg/mL, respectively ( Figure 4 ). These inhibitory potentials, even far from that of the reference compound donepezil (6.7 nM) versus AChE [ 38 ], are close to those previously published for galanthamine (2.2 µg/mL and 11.7 µg/mL) or other plant extracts [ 4 , 39 , 40 ]. Interestingly, in spite of its moderate inhibitory potential, galanthamine is a typical drug used for the treatment of Alzheimer's disease [ 41 ], validating our efforts to identify new potential inhibitory compounds.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Acorenone B showed an inhibitory activity against AChE and BChE with IC 50 concentrations of 40.8 and 10.9 μg/mL, respectively ( Figure 4 ). These inhibitory potentials, even far from that of the reference compound donepezil (6.7 nM) versus AChE [ 38 ], are close to those previously published for galanthamine (2.2 µg/mL and 11.7 µg/mL) or other plant extracts [ 4 , 39 , 40 ]. Interestingly, in spite of its moderate inhibitory potential, galanthamine is a typical drug used for the treatment of Alzheimer's disease [ 41 ], validating our efforts to identify new potential inhibitory compounds.…”
Section: Resultssupporting
confidence: 85%
“…Plants are rich in structurally diverse secondary metabolites displaying a wide range of biological activities, including possible leads for the treatment of neurodegenerative diseases [ 2 , 3 ]. Natural products have contributed greatly as sources for drug discovery for Alzheimer’s disease [ 4 ]. Earlier studies have shown that the maintenance of correct levels of acetylcholinesterases is directly related to different diseases such as Alzheimer's disease (AD), bipolar disorder, depression, and schizophrenia [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, different challenges arise during the treatment of OPs intoxications with oxime‐based drugs. One relies in the repetitive evaluation of oxime modifications to reactivate AChEs, instead of looking for new scaffolds as potential pharmacophores . For example, structure‐activity relationships (SAR) studies have reported the synthesis of 134 novel oxime‐based molecules, primarily imidazole aldoximes and hydroxymino acetamide derivatives .…”
Section: Resultsmentioning
confidence: 99%
“…One relies in the repetitive evaluation of oxime modifications to reactivate AChEs, instead of looking for new scaffolds as potential pharmacophores. [52][53][54][55] For example, structure-activity relationships (SAR) studies have reported the synthesis of 134 novel oxime-based molecules, primarily imidazole aldoximes and hydroxymino acetamide derivatives. [56] Most of them showed reasonable reactivation rates associated to ionization states that confer higher nucleophilic reactivity to the oxime group.…”
Section: Perspectives Of Novel Scaffolds As Ache Reactivatorsmentioning
confidence: 99%
“…All two-dimensional images of ligand-protein interactions were generated using LIGPLOT version 4.5.3. [ 9 ]…”
Section: Methodsmentioning
confidence: 99%